Uyghur Diaspora in Indonesia: from Nationalism to Terrorism - Chaidar, Al; Sahrasad, Herdi; Tabrani, Dedy (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2020)
Uyghurs, especially ethnic Turkestan originating from northwest China in Xinjiang province, have become a real part of jihad terror groups that are globally active. Uyghur jihadists first spread to various parts of the world when the United States and its allies attacked Afghanistan in 2001. While continuing their cooperation with the Taliban under the banner of the East Turkestan Islamic Movement (ETIM), Uyghur jihadists have now spread to Southeast Asia and the Middle East. ETIM members are part of the Turkestan Islamic Party fighting with the Al-Qaeda umbrella group in Syria, but other Uyghurs have joined ISIS in Syria and Iraq, and others have joined local terror groups in Indonesia. However, Uyghurs are currently under-examined as active participants in jihadist organizations. Their struggle against the Chinese Government or narrowly describes certain groups where Uyghurs have become participants. This paper explores the scope and scale of activities of foreign Uyghur fighters in various locations, their implications and how their participation in global jihad groups can develop in such a way.